Mini Economica Media Komunikasi Ilmu Ekonomi : Analisis Rantai Pasokan Bahan Bakar Minyak Dalam Transportasi Maritim : Studi Kasus ABC Carrier - Sulistiyaji, Fikri Tegar Devaas, Kusumastuti, Ratih Dyah (Fakultas Ekonomi dan Bisnis Universitas Indones, 2015)
This study discusses the fuel delivery process concted by ABC Carrier. Fuel delivery problem is studied because there are still some problems in the process of fuel delivery , which inhibits the supply chain network of fuel in Indonesia. To be able to deal with these problems, the research is carried out to analyze the fuel delivery process at ABC Carrier and seek the alternative solutions that can improve the efficiency of the fuel delivery process. This researchconducted using discrete event simulation using Arena simulation software version 14 by Rockwell Automation.